Electrophysiological study of young patients with exercise related paroxysms of palpitation: role of atropine and isoprenaline for initiation of supraventricular tachycardia. Issue 3 (March 1989) - Toda, I; Kawahara, T; Murakawa, Y; Nozaki, A; Kawakubo, K; Inoue, H; Sugimoto, T
Abstract : Electrophysiological studies were performed in eight patients (four men and four women, mean (SD) age 24 (5) years with paroxysmal attacks of palpitation during or immediately after exercise. Five patients were competitive athletes at college. In two patients spontaneous supraventricular tachycardia during exercise was recorded by ambulatory electrocardiographic monitoring and in another it was induced by treadmill exercise testing. Two had dual atrioventricular nodal pathways, three had manifest atrioventricular accessory pathways, and three had concealed atrioventricular pathways. Programmed stimulation induced sustained supraventricular tachycardia in six patients--in two after intravenous injection of atropine sulphate (1 mg) and in four during infusion of isoprenaline (0.01 microgram/kg/min). In one patient, non-sustained atrioventricular nodal reentrant tachycardia was induced during isoprenaline infusion. In the remaining patient, who had dual atrioventricular nodal pathways, tachycardia was not inducible. AH block prevented maintenance of reentry in five patients. In five patients shortening of the effective refractory period of the atrioventricular node with atropine (one patient) and isoprenaline (four patients) caused sustained supraventricular tachycardia. The present study indicates that treatment with atropine and isoprenaline may be an important factor in the initiation of supraventricular tachycardia in patients with exercise related paroxysms of palpitation.